Patient safety in undergraduate radiography curricula: A European perspective. Issue 1 (December 2016) - England, A.; Azevedo, K.B.; Bezzina, P.; Henner, A.; McNulty, J.P.
Abstract: Purpose: To establish an understanding of patient safety within radiography education across Europe by surveying higher education institutions registered as affiliate members of the European Federation of Radiographer Societies (EFRS). Method: An online survey was developed to ascertain data on: programme type, patient safety definitions, relevant safety topics, specific areas taught, teaching and assessment methods, levels of teaching and curriculum drivers. Responses were identifiable in terms of educational institution and country. All 54 affiliated educational institutions were invited to participate. Descriptive and thematic analyses are reported. Results: A response rate of 61.1% (n = 33) was achieved from educational institutions representing 19 countries. Patient safety topics appear to be extremely well covered across curricula, however, topics including radiation protection and optimisation were not reported as being taught at an 'advanced level' by five and twelve respondents, respectively. Respondents identified the clinical department as the location of most patient safety-related teaching. Conclusions: Patient safety topics are deeply embedded within radiography curricula across Europe. Variations exist in terms of individual safety topics including, teaching and assessment methods, and the depth in which subjects are taught. Results from this study provide a baseline for assessing developments in curricula and can also serve as a benchmark for comparisons. Highlights: First European report on patient safety (PS). PS deeply embedded within training curricula. Terms and definitions largely consistent. Some variety in the delivery and assessment methods. Report provides baseline and opportunities for comparisons.